2002
DOI: 10.1002/immu.200390018
|View full text |Cite
|
Sign up to set email alerts
|

The kidney as a second site of human C‐reactive protein formation in vivo

Abstract: C-reactive protein (CRP) is the main acute phase reactant in humans. Its production is presumably restricted to the liver but extrahepatic expression by inflamed tissue has not been studied in detail. By real-time PCR and immunohistochemistry we here show that renal cortical tubular epithelial cells (TEC) express CRP mRNA and protein within 6 h after stimulation with conditioned medium (CM) or IL-6, but not IL-1 § or TNF- § . Western blot analysis with monoclonal anti-CRP antibody that recognizes native CRP re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
106
2
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(123 citation statements)
references
References 36 publications
12
106
2
2
Order By: Relevance
“…It is also proclaimed that high HDL cholesterol levels or low LDL/HDL ratio adversely affects the release of PTX3 from adipose tissues, while high LDL cholesterol levels are correlated with high PTX3 levels (28,29). It is also emphasized that this fact could be one of the secrets behind the development of atherosclerosis (28).…”
Section: Discussionmentioning
confidence: 99%
“…It is also proclaimed that high HDL cholesterol levels or low LDL/HDL ratio adversely affects the release of PTX3 from adipose tissues, while high LDL cholesterol levels are correlated with high PTX3 levels (28,29). It is also emphasized that this fact could be one of the secrets behind the development of atherosclerosis (28).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Two studies have shown that both epithelial cells of the respiratory tract and renal epithelium produce CRP. 14,18 Moreover, neuronal cells also Figure 1. Effect of cytokine and LPS treatment on CRP protein production in HCASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, renal cortical tubular epithelial cells were shown to produce CRP after inflammatory stimuli. 14 Interestingly, CRP has also been found in human atherosclerotic plaques, 15 which could be the result of indirect deposit from circulating cells or direct production by cells in the arterial wall. We show that human coronary artery smooth muscle cells (HCASMCs), but not human umbilical vein endothelial cells (HUVECs), can synthesize CRP after stimulation by inflammatory cytokines.…”
mentioning
confidence: 99%
“…However, since anti-CRP antibodies in SLE are not directed against the circulating pentameric form of CRP but rather to CRP monomers, a more likely pathogenic potential of circulating anti-CRP would be to target tissue-bound monomeric CRP (mCRP) [22]. Such mCRP has been detected in vessels, skeletal muscle, liver and in tissue of chronic renal disease, possibly with extrahepatically produced CRP [29][30][31][32]. The well-known fact that pentameric CRP activates the classical complement pathway, has also been reported to account for mCRP [33][34][35].…”
Section: Introductionmentioning
confidence: 99%